PELATIHAN PEMANFAATAN MAGGOT SEBAGAI ALTERNATIF PENGHANCUR SAMPAH ORGANIK RUMAH TANGGA DI KELURAHAN MATA AIR KECAMATAN PADANG SELATAN, KOTA PADANG - Yenti, Melisa; Syarlinda, Fazira; Karina, Prima Dinta; Yulia, Lyra (Jurnal Hilirisasi IPTEKS, 2024)
Padang City recorded the highest amount of daily waste in West Sumatra Province, reaching 643.76 tons per day, and recorded 69.64% of household organic waste, which is often disposed of carelessly and left to pile up for days. This waste pile can cause various diseases, so it is a problem that must be resolved. Waste management is still limited and is a challenge for the environment. One solution to process and utilize household organic waste is to use the waste as feed for Maggot Black Soldier Fly (BSF). This activity aims to help the community overcome the problem of organic waste accumulation in the Waste Disposal Site (TPS) by increasing Mata Air Village residents' knowledge of organic waste management at the household level. In addition, this activity also aims to improve community independence in managing organic waste and support them in producing valuable products from household organic waste management. The methods used in this activity include counseling, demonstration of maggot cultivation practices, assistance via WhatsApp, and door-to-door visits. The results of this activity show that the community has gained new knowledge and skills to process household organic waste using maggots. The community can produce organic fertilizer and animal feed from the maggots. The conclusion of this activity shows that the training on using maggots as an alternative to managing household waste has been successful. The community can independently process their household organic waste.